MRI measurements of the thoracic aorta and pulmonary artery. Issue 1 (1st August 2017) - Beck, Leyla; Mohamed, Abdi‐Aziz; Strugnell, Wendy E; Bartlett, Harry; Rodriguez, Viviana; Hamilton‐Craig, Christian; Slaughter, Richard E
Abstract: Introduction: The purpose of this study was to obtain a range of normal measurements of the adult thoracic aorta and main pulmonary artery using cardiac MRI, and to assess agreement between measurements made on ECG‐gated two‐dimensional (2D) breath held steady‐state‐free precession (SSFP), and three‐dimensional (3D) breath held SSFP image acquisitions. Methods: Forty‐nine normal volunteers underwent cardiac MRI using a 1.5T system. Two independent examiners measured the ascending aorta, aortic arch, descending thoracic aorta and main pulmonary artery in pre‐defined locations. Results: Overall, inter‐observer agreement for all measurements was excellent. Close agreement was observed in aortic diameters obtained from the 2D and 3D SSFP methods in six of the nine aortic measurement sites. There was a tendency for the 3D measurements to be smaller than the 2D measurements but this was only significant at two sites, the aortic annulus, and the ascending aorta. There was a significance difference in aortic measurements between the left carotid artery (LC) and the left subclavian artery (LSC). Conclusion: Normal values for transverse diameters of the thoracic aorta and main pulmonary artery were established using 2D and 3D non‐contrast MR sequences in healthy adults. Overall both inter‐observer agreement, and agreement between 2D and 3D techniques was good. Mean diameter differences demonstrated at the aortic annulus, ascending aorta and aortic arch between LC and LSC although significant were less than one millimetre and unlikely to be important in clinical practice.